Frankenstein takes the cake - Rex, Adam. (Boston : Houghton Mifflin Harcourt, 2008)
Contains poems about the bad habits, anxieties, and other fears and foibles of monsters, including selections about Frankenstein's wedding.
"Sandpiper."
Bulletin of the Center for Children's Books starre
School Library Journal
Wilson's Children
Bulletin of the Center for Children's Books starre, October 2008
Horn Book, April 2009
Keywords: Children's poetry, American; Monsters -- Juvenile poetry; American poetry; Monsters -- Poetry; American poetry; Monsters -- Poetry; Picture books for children